2020
DOI: 10.3390/ijerph17134893
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Cadence on Paddling Gross Efficiency and Economy in Stand-Up Paddle Boarding

Abstract: Background: Due to the importance of energy efficiency and economy in endurance performance, it is important to know the influence of different paddling cadences on these variables in the stand-up paddleboarding (SUP). The purpose of this study was to determine the effect of paddling at different cadences on the energy efficiency, economy, and physiological variables of international SUP race competitors. Methods: Ten male paddlers (age 28.8 ± 11.0 years; height 175.4 ± 5.1 m; body mass 74.2 ± 9.4 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Previous findings showed that a lower stroke rate (approximately 45 strokes per minute) was more efficient than a higher stroke rate (55 to 65 strokes per minute) (Castañeda-Babarro et al, 2020). These authors considered the higher cadences to be less effective because they can increase instability and consequently energy consumption (Castañeda-Babarro et al, 2020). Therefore, as the stroke rate was maintained constant throughout the all-out test, it could be suggested that intensity and effort level was constant, as presented by the heart rate values.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous findings showed that a lower stroke rate (approximately 45 strokes per minute) was more efficient than a higher stroke rate (55 to 65 strokes per minute) (Castañeda-Babarro et al, 2020). These authors considered the higher cadences to be less effective because they can increase instability and consequently energy consumption (Castañeda-Babarro et al, 2020). Therefore, as the stroke rate was maintained constant throughout the all-out test, it could be suggested that intensity and effort level was constant, as presented by the heart rate values.…”
Section: Discussionmentioning
confidence: 94%
“…This could also explain the heart rate that remained stable throughout the 30 min effort, reflecting the similar stroke rate used. Previous findings showed that a lower stroke rate (approximately 45 strokes per minute) was more efficient than a higher stroke rate (55 to 65 strokes per minute) (Castañeda-Babarro et al, 2020). These authors considered the higher cadences to be less effective because they can increase instability and consequently energy consumption (Castañeda-Babarro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations